2020
DOI: 10.1002/cncr.32581
|View full text |Cite
|
Sign up to set email alerts
|

Electrocautery ablation of anal high‐grade squamous intraepithelial lesions: Effectiveness and key factors associated with outcomes

Abstract: Background Electrocautery ablation (EA) is a common treatment modality for patients with anal high‐grade squamous intraepithelial lesions (HSILs), but to the authors' knowledge its effectiveness has been understudied. The objective of the current study was to determine ablation outcomes and to identify clinicopathological factors associated with postablation disease recurrence. Methods A total of 330 people living with HIV with de novo intra‐anal HSIL who were treated with EA from 2009 to 2016 were studied ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 43 publications
0
51
0
1
Order By: Relevance
“…10 Based on the above recent series, Gaisa et al should have identified progression to ASCC in some of their patients. 4 And yet they did not. Granted, their study was not a prospective or randomized trial comparing HSIL treatment with observation to prevent cancer, and such a study currently is underway (Topical or Ablative Treatment in Preventing Anal Cancer in Patients With HIV and Anal High-Grade Squamous Intraepithelial Lesions [ANCHOR] trial; ClinicalTrials.gov identifier NCT02135419).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…10 Based on the above recent series, Gaisa et al should have identified progression to ASCC in some of their patients. 4 And yet they did not. Granted, their study was not a prospective or randomized trial comparing HSIL treatment with observation to prevent cancer, and such a study currently is underway (Topical or Ablative Treatment in Preventing Anal Cancer in Patients With HIV and Anal High-Grade Squamous Intraepithelial Lesions [ANCHOR] trial; ClinicalTrials.gov identifier NCT02135419).…”
mentioning
confidence: 99%
“…I am thrilled to report that in this issue of Cancer, Gaisa et al have presented data that point to the prevention of anal cancer by electrocautery ablation (EA). 4 In a large series of >300 people living with HIV (PLWH), the authors conducted a rigorous, albeit retrospective, study of their treatment results with EA from 2009 to 2016. 4 Not only did participants have a median follow-up of >1 year, but the study was rigorously conducted with thorough demographic data extracted, including smoking status and HIV-related parameters.…”
mentioning
confidence: 99%
See 3 more Smart Citations